If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -8x + -2 = -48 + 3x + -14 Reorder the terms: 6 + -2 + -8x = -48 + 3x + -14 Combine like terms: 6 + -2 = 4 4 + -8x = -48 + 3x + -14 Reorder the terms: 4 + -8x = -48 + -14 + 3x Combine like terms: -48 + -14 = -62 4 + -8x = -62 + 3x Solving 4 + -8x = -62 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4 + -8x + -3x = -62 + 3x + -3x Combine like terms: -8x + -3x = -11x 4 + -11x = -62 + 3x + -3x Combine like terms: 3x + -3x = 0 4 + -11x = -62 + 0 4 + -11x = -62 Add '-4' to each side of the equation. 4 + -4 + -11x = -62 + -4 Combine like terms: 4 + -4 = 0 0 + -11x = -62 + -4 -11x = -62 + -4 Combine like terms: -62 + -4 = -66 -11x = -66 Divide each side by '-11'. x = 6 Simplifying x = 6
| 3x=4+3x-1 | | 10x-(2x+4)=60 | | -(12-2x)=-7 | | .2x+c=6 | | x^2-12x+81=0 | | 0.5(4-3)2=x | | 0.5(4-1)2=x | | 0.5(5-3)2=x | | 0.5(5-3)=x | | 0.5(5-2)2= | | y+2.9=5.65 | | 0.5(5-3)2= | | 0.5(5-3)= | | Ln(7)-ln(x)=-0.06 | | 3(6-4r)=7(-7-r) | | u-9.45=3.29 | | 2x(lnx)+2=0 | | x-4.71=6.9 | | x-4.71=69 | | w+2.2=8.87 | | u-12.8=8 | | x=9+-5 | | 8x+7y+9z=1 | | -2.7+a=-6.4 | | 15m^2-6m=0 | | 5i(2i-7)=0 | | 43+78= | | 5cos(x+1)=1 | | 2(4x+3)(3x+5)= | | 2(4x+3)(3x+5)=X^2+58x+B | | 38a+14=15 | | 8s^2-80s+30=-10 |